PENDAMPINGAN PEMBUATAN PROPOSAL PENELITIAN TINDAKAN KELAS (PTK) PADA GURU DI SMA SRIJAYA NEGARA PALEMBANG - Dewi Pratita; Dewi Koryati; Ikbal Barlian; deskoni deskoni (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2019)
Abstract The teaching profession is a complex and challenging profession. In addition it must be competent and mastered the science that was involved, teachers also charged must be capable of creative, innovative, and inspiring when teaching in the classroom. It is not easy to become a professional. As a professional teacher who dedicated himself to education, teachers must be routinely adding their knowledge by reading and writing. Thereby you can summarize the valuable experience for the important things like understanding the instructional design, understanding learning styles of students, as well as the utilization of the internet in learning. Activities conducted by teachers such as these can be poured in a classroom research conducted by teachers through Classroom Action Research activities or better known as PTK. The purpose of the the activities of this devotion is producing material on how that can be done by teachers in improving the professionalism of teachers in the High School State Srijaya Palembang through Class Action Research Activities (PTK). This devotion activities carried out in the High School State Srijaya Palembang and followed by 20 teachers from a variety of different fields of study. A model of devotion used was mentorship with methods of delivery of material concerning the Class Action Research (PTK). Evaluation test of understanding PTK with an average of 50 increased to 58.5 in the final test. The increase in accompanied by a very strong interest of participants to be able to make and carry out research activities actions class amounted to 87%. The conslusion of this activity the participants enthusiastically follow the activities of mentoring to improve the ability of professional teachers. Abstrak Profesi guru adalah profesi yang kompleks dan menantang. Di samping harus kompeten dan menguasai bidang ilmu pengetahuan yang digeluti, guru juga dituntut harus mampu kreatif, inovatif, serta inspiratif ketika mengajar di kelas. Tidak mudah untuk menjadi professional. Sebagai guru professional yang mendedikasikan dirinya bagi pendidikan, guru harus rutin menambah ilmunya dengan membaca dan menulis. Dengan demikian dapat merangkum pengalaman berharga untuk hal-hal penting seperti memahami desain pembelajaran, memahami gaya belajar siswa, serta pemanfaatan internet dalam pembelajaran. Kegiatan yang dilakukan oleh guru seperti ini dapat dituangkan dalam suatu penelitian di dalam kelas yang dilakukan oleh guru melalui kegiatan Penelitian Tindakan Kelas atau yang lebih dikenal dengan istilah PTK. Tujuan dari kegiatan Pengabdian ini adalah menghasilkan materi tentang cara yang dapat dilakukan oleh guru dalam meningkatkan profesionalisme guru di SMA Srijaya Negara Palembang melalui kegiatan Penelitian Tindakan Kelas (PTK). Kegiatan Pengabdian ini dilaksanakan di SMA Srijaya Negara Palembang dan diikuti oleh 20 orang guru dari berbagai bidang studi yang berbeda. Model Pengabdian yang digunakan yaitu pendampingan dengan metode penyampaian materi mengenai Penelitian Tindakan Kelas (PTK). Evaluasi tes awal mengenai pemahaman PTK dengan rata - rata 50 meningkat menjadi 58.5 pada tes akhir. Peningkatan tersebut di iringi dengan minat yang sangat kuat dari peserta untuk dapat membuat dan melaksanakan kegiatan Penelitian Tindakan Kelas (PTK) sebesar 87%. Kesimpulan dari kegiatan ini peserta antusias mengikuti kegiatan pendampingan untuk dapat meningkatkan kemampuan profesional guru.